Metabolic alterations induced by high maternal BMI and gestational diabetes in maternal, placental and neonatal outcomes - Martino, Jole (2013)
Maternal obesity and diabetes increase the risk of delivering large for gestational age infants (LGA), who have higher risk of long term obesity or metabolic syndrome [1]. As the underpinning mechanisms of how fetal growth is regulated by the placenta remain unclear [2], this thesis has investigated placental responses to high maternal BMI and gestational diabetes.